THE EXPERIENCER ROLE IN GERMAN AND INDONESIANS SENTENCES - Widodo, Pratomo (Kajian Linguistik dan Sastra, 2009)
This article is based on a study about the experiencerâs role in the German andIndonesian sentences. This study deals with: (a) the kind of verbs which require theexperiencer role constituent, (b) the realization of experiencer role in the syntacticfunctions , and (c) the differences and similarities of the syntactic and semantic behavior between German and Indonesian sentences which consist experiencer roleconstituent.Keywords: experience role, syntactic functions